Life Trajectories in the Language Games of Islamic Reform and Pentecostalism in Cape Town - Tayob, Abdulkader (Journal for the study of religion, 2023)
I present two individuals in Cape Town as they became religious leaders in Islamic reform and Christian Pentecostalism respectively. This essay pays attention to the place of charisma generated in their practices, how they relate to existing traditions and institutions, and how they introduce innovations over their life trajectories. Unlike most studies on Pentecostalism and Islamic reform, this essay analyses lesser-known leaders in their respective congregations and communities to illustrate what Wittgenstein has called a ‘language game’. The latter offers a perspective on how individuals inhabit a movement without being constrained by it. The language games of these movements come alive in the life trajectories of my subjects.